2013
DOI: 10.1891/1058-1243.22.4.234
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Maternity Care: Can New Dogs Learn Old Tricks?

Abstract: In this article, a Lamaze Certified Childbirth Educator describes her efforts to change the culture of birth in a community hospital in a small Midwestern town. Her experience highlights the challenges and the frustrations involved in creating change. The authors reflect on ways to enhance the success of change and advocacy strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The participants believed that health providers may refuse to accept new care because they do not have the needed skills to do new practices, Belizan et al ( 18 ). Furthermore, changing a complex process requires commitment and strong, relentless, and creative leadership within the institution ( 19 ). Another barrier at this level was lack of authority to make decisions by midwives.…”
Section: Discussionmentioning
confidence: 99%
“…The participants believed that health providers may refuse to accept new care because they do not have the needed skills to do new practices, Belizan et al ( 18 ). Furthermore, changing a complex process requires commitment and strong, relentless, and creative leadership within the institution ( 19 ). Another barrier at this level was lack of authority to make decisions by midwives.…”
Section: Discussionmentioning
confidence: 99%
“…Care should be culturally sensitive and equitable (Oosthuizen et al, 2017). Curl & Lothian, 2013 found that generational characteristics amongst midwives influenced to some extent the culture of service delivery during childbirth with younger nurses being more abusive and disrespectful. Practice should be supported by top leadership as well as policies and protocols that reflect best evidence and having responsive healthcare systems (Bingham & Main, 2010;Mwaniki et al, 2014).…”
Section: Clinical Audits and Feedbackmentioning
confidence: 99%